Pengaruh Insentitas Research and Development (R&D) - Hajrah, Hajrah; Amelia Rezki Septiani Amin, Mira Mira , (SEIKO : Journal of Management & Business, 2025)
This study aims to analyze the effect of Research and Development (R&D) intensity on the financial performance of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The type of research used is quantitative exploratory. The data source used is secondary data. The sample used is purposive sampling. The results of the study indicate that Research and Development (R&D) intensity has a significant positive effect on financial performance, as measured by Return On Asset (ROA). This finding identifies that companies that increase investment in Research and Development (R&D) tend to experience increased profitability and competitiveness in the market. This study provides recommendations for company management to further optimize Research and Development (R&D) activities as a strategy to improve financial performance and competitiveness of companies in an increasingly competitive industry. Keywords: Research and Development (R&D) Intensity, Financial Performance